2018
DOI: 10.1002/cssc.201801433
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Crystallinity of Low‐Temperature Solution‐Processed SnO2 for Highly Reproducible Planar Perovskite Solar Cells

Abstract: Low-temperature solution-processed SnO as a promising electron-transport material for planar perovskite solar cells (PSCs) has attracted particular attention because of its outstanding properties such as high optical transparency or high electron mobility. However, low-temperature sol-gel processes used in the synthesis are inevitably affected by the humidity of the atmosphere, which results in a wide distribution in the performance of the prepared PSCs owing to the inability to control crystallinity and defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…The residual Cl À on the surface leads to partial decomposition of perovskite. 26 The XRD of the perovskites validates the PbI 2 existence (Fig. S2d †).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The residual Cl À on the surface leads to partial decomposition of perovskite. 26 The XRD of the perovskites validates the PbI 2 existence (Fig. S2d †).…”
Section: Resultssupporting
confidence: 59%
“…[13][14][15][16][17] Among the candidates, SnO 2 exhibits salient features, such as wide optical band gap (3.6-4.0 eV), good transparency, high mobility up to 240 cm 2 V À1 s À1 , excellent chemical stability, and easy lowtemperature preparation. [18][19][20] There have been many reported processes for preparing SnO 2 ETLs, embracing spin-coating, [21][22][23][24][25][26] slot die coating, 27 atomic layer deposition, 28,29 chemical bath deposition, 30,31 sol-gel method, [32][33][34] etc. Besides, all methods above require a proper temperature treatment in the fabrication process or post-treatment, and sometimes even involve a high temperature annealing.…”
Section: Introductionmentioning
confidence: 99%
“…There is also exclusive superiority for PSC in tandem solar cells (Leijtens et al, 2018;Zhao et al, 2018a;Albrecht et al, 2016;, semitransparent solar cells (Xue et al, 2018;Zhang et al, 2018;Xie et al, 2018), and flexible devices (Feng et al, 2018;Bu et al, 2018). However, the instability of perovskite absorber materials (Correa-Baena et al, 2017) and difficulty in large area fabrication devices (Li et al, 2018b) is still serious problems for future commercialization of p e r o v s k i t e -b a s e d s o l a r c e l l . So far, the planar n-i-p structured PSCs (Halvani Anaraki et al, 2018;Yang et al, 2018a) shows great promise due to their easier upscaling deposition of electron transport layers (ETLs) compared to mesostructured PSCs (Petrović et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…And there are lots of fabrication methods (Chen et al, 2019) have been reported to efficiently deposit thin ETL films, however, not all the methods are suitable for achieving uniform large area high quality thin films for large area perovskite solar modules (PSMs). For example, solution based preparation methods such as spin-coating (Yang et al, 2018b) and chemical bath deposition (Anaraki et al, 2016) suffer from necessary annealing process, and the quality of the sintered films are sensitive to the external environmental conditions including humidity (Li et al, 2018a;Bu et al, 2016), oxygen and, etc., which results in poor reproducibility and is fatal to industrial production. Another widely reported method of atomic layer deposition (Wang et al, 2016;Correa Baena et al, 2015) (ALD) to fabricate ETLs for PSCs exhibits excellent stability and reproducibility, which can be attributed to the homogeneity of monolayer deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The majorityo fh igh-efficiency PVSCsr eported so far have utilized the conventional n-i-p device configurationw ith titanium dioxide (TiO 2 )o rs tannic oxide (SnO 2 )a sE TLs. [18][19][20] However,t he preparation of those inorganic n-type semiconducting metal oxide ETLs involves high-temperature sintering, especially fort he mesoporousT iO 2 scaffold, whichr equires more than 450 8Ct os inter. [21,22] This has negative effects on mass production and flexible device architecture.…”
Section: Introductionmentioning
confidence: 99%